An approach to promote the uptake of evidence on agricultural research using strengthened relationships with national institutes and data systems - CGIAR Research Program on Policies, Institutions, and Markets (2019)
A 2019 Discussion Paper based on the three country study provides recommendations for increasing the uptake of evidence on agricultural research at country level. A key recommendation is to invest in building strong relationships and networks to institute linkages with official national data systems.